Lab-on-a-Film disposable for genotyping multidrug-resistant Mycobacterium tuberculosis from sputum extracts. Issue 7 (25th February 2019) - Kukhtin, Alexander C.; Sebastian, Thomas; Golova, Julia; Perov, Alex; Knickerbocker, Christopher; Linger, Yvonne; Bueno, Arial; Qu, Peter; Villanueva, Michael; Holmberg, Rebecca C.; Chandler, Darrell P.; Cooney, Christopher G.
Abstract : Multiplex PCR and hybridization occur within a closed-amplicon laminate, which includes gel arrays printed on unmodified and untreated plastic film. Abstract : We describe a Lab-on-a-Film disposable that detects multidrug-resistant tuberculosis (MDR-TB) from sputum extracts. The Lab-on-a-Film disposable consists of 203 gel elements that include DNA sequences (probes) for 37 mutations, deletions, or insertion elements across 5 genes (including an internal control). These gel elements are printed on a flexible film, which costs approximately 500 times less than microarray glass. The film with printed gel elements is then laminated to additional rollable materials (films) to form a microfluidic flow cell. We combined multiplex amplification and hybridization steps in a single microfluidic chamber, without buffer exchanges or other manipulations up to and throughout hybridization. This flow cell also incorporates post hybridization wash steps while retaining an entirely closed-amplicon system, thus minimizing the potential for sample or amplicon cross-contamination. We report analytical sensitivity of 32 cfu mL −1 across all MDR-TB markers and detection of MDR-TB positive clinical specimens using an automated TruTip workstation for extraction and the Lab-on-a-Film disposable for amplification and detection of the extracts.